PENDAMPINGAN PENINGKATAN KAPASITAS APARATUR DESA DAN MASYARAKAT DESA LABUHAN RATU IX KECAMATAN LABUHAN RATU KABUPATEN LAMPUNG TIMUR MENUJU OPTIMALISASI PROGRAM SDGs NASIONAL - Permatasari, Ermanita; Fatimah, Siti; Trismahwati, Dewi; Kholijah, Siti; damanhuri , Damanhuri (LPPM STAI DARUSSALAM LAMPUNG, 2023)
Improving the competitiveness of village government is the main pillar in achieving SDGs as a form of commitment and mainstreaming village development that guarantees justice and village governance that is able to improve the quality of life from one generation to the next. Consideration of providing assistance to increase the capacity of village apparatus and the community of Labuhan Ratu IX Village, Labuhan Ratu District, East Lampung Regency towards optimizing the national SDGs program, namely to support and increase the various potentials possessed by the Village towards achieving SDGs. With the Assistance, Counseling, and Training provided to Village Apparatuses and Communities such as Legal Product Making Training, Capacity Building for Village Apparatuses in the Field of Information and Technology, MSME Training and Assistance, Legal Consultation and Religious Guidance, it is hoped that this can realize Optimization of the Sustainable Development Program National SDGs, so that they can increase the human resource capacity of the Village Apparatus and improve the Economy and Food Security of the Community of Labuhan Ratu IX Village.